The Phenomenon of Border Dispute Resolution in Elpaputih Sub-District - Suat, Hatty; Borut, Muhamad (LPPM Institut Pendidikan Nusantara Global, 2025)
The perspective of Central Maluku Regency and West Seram Regency in resolving boundary conflicts in Elpaputih District in its development continues to be an interesting phenomenon to be studied, which until now has not answered the demands of the community in a solution that is as expected. The Regional Government is considered unable to provide the best solution to resolve the boundary conflict, so it attracts attention to be researched and studied in depth. From the results of qualitative assessment in this study, several strategic steps need to be taken by local governments in resolving border conflicts in Elpaputih District, namely First. realizing recognition, namely both parties (District Government) must recognize the reality and conflict situation that occurs between them (recognition of the interests fought by the community). Second, considering interests, namely the government needs to accommodate the interests that are fought for must be neatly organized, not scattered and compartmentalized so that each party does not feel disadvantaged by government decisions and clearly understands the scope of interests and needs of the community. Third, building an agreement, namely the two parties (District Government) agree on the rules of the game which become the basis and guide in relations and interactions between the government and the community. Fourth, prioritizing firmness, namely the government must be wise and firm in executing every decision that has been agreed upon by prioritizing socialization in a reel to the community.